3D modeling of esophageal development using human PSC-Derived basal progenitors reveals a critical role for notch signaling - Zhang, Yongchun (2018)
Pluripotent stem cells (PSCs) could provide a powerful system to model development of the human esophagus, whose distinct tissue organization compared to rodent esophagus suggests that developmental mechanisms may not be conserved between species. We therefore established an efficient protocol for generating esophageal progenitor cells (EPCs) from human PSCs. We found that inhibition of TGF-ß and BMP signaling is required for sequential specification of EPCs, which can be further purified using cell-surface markers. These EPCs resemble their human fetal counterparts and can recapitulate normal development of esophageal stratified squamous epithelium during in vitro 3D cultures and in vivo. Importantly, combining hPSC differentiation strategies with mouse genetics elucidated a critical role for Notch signaling in the formation of this epithelium. These studies therefore not only provide an efficient approach to generate EPCs, but also offer a model system to study the regulatory mechanisms underlying development of the human esophagus.